2018
DOI: 10.1016/j.jtcvs.2017.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival in octogenarians after mitral valve surgery for degenerative disease: The Mitral Surgery in Octogenarians study

Abstract: ObjectivesAn increasing number of octogenarians are referred to undergo mitral valve surgery for degenerative disease, and percutaneous approaches are being increasingly used in this subgroup of patients. We sought to determine the survival and its predictors after Mitral Valve Surgery in Octogenarians (MiSO) in a multicenter UK study of high-volume specialized centers.MethodsPooled data from 3 centers were collected retrospectively. To identify the predictors of short-term composite outcome of 30 days mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 38 publications
7
50
1
Order By: Relevance
“…After propensity score matching, the preoperative demographic data were similar between the 2 groups. Despite the concerns that have been raised in this regard, CPB and ACC times were not significantly longer in the MV repair group before or after propensity score matching, which is similar to previous studies [36]. The CPB and ACC times (199±76.5 minutes and 127±50.9 minutes, respectively) were markedly longer than those reported in previous studies [38].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…After propensity score matching, the preoperative demographic data were similar between the 2 groups. Despite the concerns that have been raised in this regard, CPB and ACC times were not significantly longer in the MV repair group before or after propensity score matching, which is similar to previous studies [36]. The CPB and ACC times (199±76.5 minutes and 127±50.9 minutes, respectively) were markedly longer than those reported in previous studies [38].…”
Section: Discussionsupporting
confidence: 79%
“…However, the feasibility and efficacy of MV repair in the elderly population is still debated. Although some retrospective observational studies and meta-analyses have suggested that MV repair might have favorable results in early and long-term outcomes even in the elderly population [310], data obtained from administrative American databases showed a low rate of MV repair (<50%) in those older than 65 years [13,14]. Some operators, especially young surgeons, still considered older patients to be poor surgical candidates for MV repair for multiple reasons: (1) MV repair requires longer CPB and ischemic times, which can affect early and long-term clinical outcomes; (2) elderly patients tend to have a more friable or calcified leaflet and annulus, making repair technically more difficult, increasing the possibility of failure and reoperation; and (3) the shorter life expectancy of elderly patients may decrease the benefit of MV repair over MV replacement [5,8,9,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] A high logistic Euroscore II (LES) resulted in a higher incidence of postoperative complications. 8,9 Furthermore, the actual clinical retrospective studies assess only the learning curve without considering the impact of a high BMI and LES in the learning curve. [10][11][12][13][14][15] While the increased demand for MIMVS leads surgeons to venture in minimally invasive programs, there are still controversies regarding the appropriate timing to introduce high-risk patients in their clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, there are some operative factors that could have contributed to overbalance the results in favor of MVr in the study by Chivasso and colleagues. 2 For example, it is unknown if the mitral valve apparatus was spared during surgery and not clear why 18 patients received a small-sized prosthesis (23 and 25 mm).…”
mentioning
confidence: 99%